The philosophical basis and artistic characteristics of contemporary Western painting - Wang, Jiawei (Transformação, 2024)
The guiding role of philosophical thinking, in artistic creation and development, is one of the important factors determining the direction of contemporary painting art. Different philosophical perspectives and trends have had a profound impact on the artists’ perspectives and creative methods. The characteristics of contemporary Western painting art demonstrate the subversion and alienation of tradition, and highlight individual and ethnic characteristics. The study explores the artistic characteristics and philosophical origins of contemporary Western painting as the main direction, and analyzes the impact of modern aesthetics, art markets and philosophical thinking on Western modern art. This diversity makes contemporary Western painting works more diverse and complex, blending with contemporary society and aesthetic tastes, constantly promoting the development and changes of art. Resumo: O papel orientador do pensamento filosófico, na criação e desenvolvimento artísticos, é um dos fatores importantes que determinam a direção da arte da pintura contemporânea. Diferentes perspectivas e tendências filosóficas tiveram um impacto profundo nas perspectivas e nos métodos criativos dos artistas. As características da arte contemporânea da pintura ocidental demonstram a subversão e a alienação da tradição e realçam as características individuais e étnicas. O estudo explora as características artísticas e as origens filosóficas da pintura ocidental contemporânea, como direção principal, e analisa o impacto da estética moderna, dos mercados de arte e do pensamento filosófico na arte moderna ocidental. Essa diversidade torna as obras de pintura ocidental contemporânea mais diversificadas e complexas, misturando-se com a sociedade contemporânea e os gostos estéticos, promovendo constantemente o desenvolvimento e as mudanças da arte.